2006
DOI: 10.1074/jbc.m600320200
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 Represses Peroxisome Proliferator-activated Receptor-γ1 and -γ2 Gene Promoters in Primary Adipocytes

Abstract: FOXO1 and peroxisome proliferator-activated receptor-␥ (PPAR␥) are crucial transcription factors that regulate glucose metabolism and insulin responsiveness in insulin target tissues. We have shown that, in primary rat adipocytes, both factors regulate transcription of the insulin-responsive GLUT4 gene and that PPAR␥2 detachment from the GLUT4 promoter upon thiazolidinedione binding up-regulates GLUT4 gene expression, thus increasing insulin sensitivity (Armoni, M., Kritz, N., Harel, C., Bar-Yoseph, F., Chen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(189 citation statements)
references
References 26 publications
8
179
1
1
Order By: Relevance
“…Reducing transcription of the glucose reporter GLUT4 by PPARg can lead to a decrease in insulin sensitivity in adipocytes (Armoni et al, 2003). Thus in addition to inhibiting differentiation, FOXO1 activation leads to upregulated GLUT4 levels and a further increase in cellular insulin sensitivity (Armoni et al, 2006(Armoni et al, , 2007. Evidence also suggests that FOXO1 might function as a coactivator of PPARa in myocytes.…”
Section: Regulation Of Glucose and Fatty Acid Metabolism By Foxo-intementioning
confidence: 97%
“…Reducing transcription of the glucose reporter GLUT4 by PPARg can lead to a decrease in insulin sensitivity in adipocytes (Armoni et al, 2003). Thus in addition to inhibiting differentiation, FOXO1 activation leads to upregulated GLUT4 levels and a further increase in cellular insulin sensitivity (Armoni et al, 2006(Armoni et al, , 2007. Evidence also suggests that FOXO1 might function as a coactivator of PPARa in myocytes.…”
Section: Regulation Of Glucose and Fatty Acid Metabolism By Foxo-intementioning
confidence: 97%
“…Therefore, reducing FoxO1 mRNA expression may lead to improvements in Pparc activity. Furthermore, it has been reported that FoxO1 can inhibit PPARc1 and PPARc2 promoter activity through direct interaction between FoxO1 and PPARc promoter [94]. Therefore, FoxO1 may suppress PPARc expression at the transcriptional level.…”
Section: Adipose Tissuesmentioning
confidence: 99%
“…In adipocytes, PPAR␥ gene expression is under inhibitory control by FoxO1 (11,12). FoxO1 is a member of the family of winged-helix/forkhead transcription factors that serve important roles in cellular differentiation, proliferation, apoptosis, and the response to cellular stress in many tissues.…”
Section: Peroxisome Proliferator-activated Receptor ␥ (Ppar␥)mentioning
confidence: 99%